Human Capital Performance in Manufacturing Companies in Indonesia: Analysis of the Influence of Team Work Management and Work satisfaction - Siregar, Robert Tua; Pantas, Hendrick; Sudirman, Acai (IJBLE Scientific Publications Community Inc., 2024)
The manufacturing industry requires skilled human resources personnel who can work effectively in teams and have high work satisfaction because these factors can contribute significantly to the company's performance and competitiveness. The main objective of this study is to analyze the effect of teamwork management and work satisfaction on human capital performance in manufacturing companies. The sample used was 200 respondents, as determined by the purposive sampling method. The study's results confirmed that teamwork management and work satisfaction positively and significantly affect human capital performance. Management that supports this collaboration can reduce stress levels and increase employee engagement, which strengthens the company's performance and competitiveness of human capital. In addition, work satisfaction can also reduce stress levels and employee turnover, contributing to the stability and efficiency of human capital. This study's results are expected to guide manufacturing companies in building stronger and more competitive human resources, ultimately supporting economic growth and Indonesia's position in the global supply chain